Mercado de trabalho no Nordeste: o legado da ação do Estado. Uma análise do Estado do Ceará - Leite, Ana Cristina Teixeira (1988)
The-main objective of this paper is to understand the role of the Governrnentas a factor that influences in the developnent of the production force andjconsequently, in the evolution of the industriali~ation degree in a certain economic area. This economic area was defined as the metropolitan region of Fortaleza, where the influence of the Govennmentis so much, not only on the productive structure, but also with a dírect perfonnance, as an employer. Considering that in the undeveloped couDtries the Government acts as an agent in the development, we find that i ts action is rruch more complex, once i t influences on the -deve Ioprnerrtof the productive force, not only in a indirect way - by economic politics -, but also in a direct way - "M1enthe producing Goverrmerrtappears. Conceming the North-east, and particularly lhe Metropo li tan region of Fortaleza, the action of the Governmentwas charac teri zed , sínce. the colonial period, by an attitude, above all, patemalist - and assistancelist, aiming - besides-the inspectíon -, make the effects of the periodic dryings smaller. This way of aet íng of the Govemment -suppbrted, also, by the local poli tical groups - took to the conformation of a productive st.ruc ture' wher-ethe agrarian and corrmercial capital prevails. The maintenance of a productive structure, Wiere a low degree of industrialization prevails, a develop~d service sector, but with a low production -althougj1 it presents modemized areas -, andan agrarian structure that stimulates the country-side-city expulsion, takes to the confonnation of an incipient labour market, leading to a high unemploymentand subemploymentrate. The action of the Govemment, inattentive to the fonnation of this kind of structure, Leads ,' on the other hand, to the expansion of é!! .er ki o